Peran Kebijakan Dividen dalam Memediasi Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan - Sayoga, Raditya; Sulistyo, Sulistyo; Yogivaria, Doni Wirshandono (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
The purpose of this study was to test and determine the effect of company size, debt policy, profitability, and free cash flow on firm value through dividend policy as an intervening variable in energy sector companies listed on the IDX for the period 2018-2022. This research is a quantitative type that uses secondary data in the form of numbers in financial reports. Implementation of research on 14 energy sector companies with sample acquisition through purposive sampling. The analytical method used is path analysis after fulfilling the prerequisite test for classical assumptions in the SPSS version 23 aplication. The results of the research show that company size has no impact on dividend policy, debt policy has no impact on dividend policy, profitability has an effect an dividend policy, free cash flow has an effect. Company size, debt policy, and profitability has an effect on company value. Free cash flow and dividen policy has no impact on company value. Furthermore, dividend policy as an intervening variable cannot mediate the influence of company size, debt policy, profitability, and free cash flow on company value.